Querencia : reflections on the New Mexico homeland - Fonseca-Chávez, Vanessa (Querencias series., 2020)
This collection of both deeply personal reflections and carefully researched studies explores the New Mexico homeland through the experiences and perspectives of Chicanx and indigenous/Genízaro writers and scholars from across the state.